Pengaruh penggunaan lembar kerja siswa (LKS) terhadap hasil belajar tema 4 siswa kelas V SD Se-Gugus IV Ngurah Rai - Nuthafsari, Refni Avianti; Wahyuningsih, Siti; Karsono, Karsono (Jurnal Pendidikan Dasar, 2022)
This study aims to determine the effect of the use of student’s worksheet on learning outcomes theme 4 in Grade V Odd Semester students. This study is a quasi-experimental study with non- equivalent control group design. The population of this study were students of Grade V Elementary School in Cluster IV District Laweyan, Surakarta. The sample used two elementary schools: SDN Bumi 1 Surakarta as experimental class and SDN Pajang IV as control class. The data of this study used a test instrument learning outcomes theme 4 in the form of objective tests. The test results were then analyzed by testing the paired sample t test. The results of the paired sample t test showed that the experimental group output obtained 0.000 < 0.05 which means there is a difference in the average learning outcomes in pre-test with post-test, while the control group output obtained 0.347 > 0.05 which means there is no difference in the average student learning outcomes for pre-test with post-test. Based on the results it can be concluded that there is an influence between the use of student worksheets on the learning outcomes of theme 4 V SDN Bumi 1 academic year 2021/2022.